Modification of polyamide membrane surface with chlorine dioxide solutions of differing pH - Alayemieka, Erewari; Lee, SeockHeon (DESALINATION PUBL, 2012)
Free chlorine is the common biocide used in the membrane desalination industry. However, it is incompatible with polyamide membranes. Chlorine dioxide (ClO2) is an effective biocide and is more compatible with polyamide membranes. The effects of ClO2 on polyamide membrane hydrophillicity and surface charge were studied under static soaking conditions. Membrane coupons were soaked in acidic, neutral, and alkaline pHs of ClO2. The membrane's hydrophilicity and surface charge were assessed by dynamic contact angle and streaming potential analyzer respectively, while performance was analyzed on a bench scale desalination system. The result of the experiment showed that ClO2 influenced membrane hydrophilicity and surface charge. Hydrophilicity improved irrespective of ClO2 pH, whereas surface charge was either suppressed or improved depending on ClO2 pH. Permeate flux increased for acidic, neutral, and alkaline conditions by 34%, 34%, and 77%, respectively. A slight trade-off in salt leakage for acidic and alkaline pH conditions was observed. The phenomenal performance of ClO2 oxidized membrane was influenced by modifications in both the membrane surface and chemical characteristics.
Keywords: HYPOCHLORITE DEGRADATION; AROMATIC POLYAMIDES; OSMOSIS; PERFORMANCE; DISINFECTION; OXIDATION; SEAWATER